KEPASTIAN HUKUM TERHADAP PUTUSAN PENUNDAAN KEWAJIBAN PEMBAYARAN HUTANG - halimi, muhammad yusuf (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2024)
The existence of legal certainty in the context of decisions to postpone debt payment obligations is the main basis in the legal system which functions to regulate the rights and obligations between creditors and debtors. Postponement of debt payment obligations is a legal mechanism that provides debtors with the opportunity to overcome financial difficulties by maintaining business continuity without eliminating payment responsibilities to their creditors. However, legal certainty in implementing the decision to postpone debt obligations is a concern because it affects both parties. The aspect of legal certainty in this case includes aspects of protection of creditor rights as well as clarity of procedures that must be followed by debtors in managing their finances again. Consistent and clear law enforcement is needed to ensure that debt suspension decisions are not misused or avoided by parties who should be responsible. Transparent and fair actions of the judicial system are essential to maintain legal certainty, ensuring that the rights of both parties are respected. Apart from that, legal certainty also influences trust in the financial system as a whole. A high level of certainty will increase investor confidence and encourage economic growth, while uncertainty can hinder investment and economic growth. Thus, legal certainty regarding decisions to postpone debt payment obligations is very important in building a legal environment that is fair, transparent and adequate for all parties involved.Keywords: Postponement of Debt Payments, Legal Certainty, Creditor Protection 1 ABSTRAK :Keberadaan kepastian hukum dalam konteks putusan penundaan kewajiban pembayaran hutang merupakan landasan utama dalam sistem hukum yang berfungsi untuk mengatur hak dan kewajiban antara pihak kreditor dan debitur. Penundaan kewajiban pembayaran hutang adalah mekanisme hukum yang memberikan kesempatan kepada debitur untuk mengatasi kesulitan keuangan dengan menjaga keberlangsungan usaha tanpa menyingkirkan tanggung jawab pembayaran kepada kreditornya. Namun, kepastian hukum dalam implementasi putusan penundaan kewajiban hutang menjadi perhatian karena mempengaruhi kedua belah pihak. Aspek kepastian hukum dalam hal ini mencakup aspek perlindungan terhadap hak kreditor serta kejelasan prosedur yang harus diikuti oleh debitur dalam mengelola kembali keuangannya. Penegakan hukum yang konsisten dan jelas diperlukan untuk memastikan bahwa putusan penundaan hutang tidak disalahgunakan atau dihindari oleh pihak yang seharusnya bertanggung jawab. Tindakan yang transparan dan adil dari sistem peradilan sangat penting agar kepastian hukum terjaga, memastikan bahwa hak- hak kedua belah pihak dihormati. Selain itu, kepastian hukum juga mempengaruhi kepercayaan dalam sistem keuangan secara keseluruhan. Tingkat kepastian yang tinggi akan meningkatkan kepercayaan investor dan mendorong pertumbuhan ekonomi, sementara ketidakpastian dapat menghambat investasi dan pertumbuhan ekonomi. Dengan demikian, kepastian hukum terhadap putusan penundaan kewajiban pembayaran hutang sangatlah penting dalam membangun lingkungan hukum yang adil, transparan, dan memadai bagi semua pihak yang terlibat.Kata k